2008
DOI: 10.4103/0019-5545.39756
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal behavior amongst adolescent students in south Delhi

Abstract: Objective:To study the prevalence of suicidal behavior and its epidemiological correlates amongst adolescent students in south Delhi.Settings and Design:A cross-sectional study in three schools and two colleges in south Delhi.Participants:A total of 550 adolescent students aged 14 to 19 years selected by cluster sampling.Statistical Analysis:Proportions, chi square test, bivariate logistic regression.Results:About 15.8% reported having thought of attempting suicide, while 28 (5.1%) had actually attempted suici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 10 publications
4
32
3
Order By: Relevance
“…6 In similar studies among adolescents in South Delhi almost 50% boys reported being involved in a physical fight and 15.8% reported having thought of attempting suicide in past 12 months. 7,8 In compare to a similar study of urban and rural school students of Kolkata, our studies reported slightly less issues of mental health and physical factors while protective issues are slight less in urban students and slight higher in rural students.…”
Section: Discussioncontrasting
confidence: 51%
“…6 In similar studies among adolescents in South Delhi almost 50% boys reported being involved in a physical fight and 15.8% reported having thought of attempting suicide in past 12 months. 7,8 In compare to a similar study of urban and rural school students of Kolkata, our studies reported slightly less issues of mental health and physical factors while protective issues are slight less in urban students and slight higher in rural students.…”
Section: Discussioncontrasting
confidence: 51%
“…5 According to Sharma, Grover and Chaturvedi study showed about 15.8% having thought of attempting suicide, 5.1%had actually attempted suicide which used a pre-tested, semi-open-ended and self-administered questionnaire which is almost similar to our study. 13 Nearly 5.5% of the age group 13-17 years reported high suicidal risk and suicidal ideation according to National Mental Health Survey reports of NIMHANS 2016. 11 The prevalence of ADHD (Attention Deficit Hyperactive Disorder) in our study was highest among urban high school participants i.e.…”
Section: Discussionmentioning
confidence: 99%
“…[18,21] In a large study from Guyana, 18.4% of students considered suicide in the last one year. [22] In another study from Nigeria, suicidal ideas were reported in 20% of the students, and suicidal attempt, in 12%.…”
Section: Students Stress and Suicidal Ideasmentioning
confidence: 99%
“…Sharma et al also reported correlation of mother's working status with suicidal ideas in a study conducted in Delhi. [21] This finding indicates that students whose mothers are working Þ nd it difÞ cult to cope with problems of student life. In an earlier study, having close friends and understanding parents was negatively associated with suicide ideation.…”
Section: Students Stress and Suicidal Ideasmentioning
confidence: 99%